Genome survey sequencing and identification of genomic SSR markers for Rhododendron micranthum - Zhou, Xiao-jun (Biosci Rep, 2020)
Rhododendron micranthum is an evergreen shrub species widely distributed in China that has high ornamental and medicinal value. However, there is a lack of molecular and genomic data for this plant, which severely restricts the development of its relevant research. The objective of the present study was to conduct a first genomic survey of R. micranthum and determine its whole-genome sequencing scheme. Next-generation sequencing (Illumina Hi-Seq Xten) was used to measure the genome size of R. micranthum, K-mer analysis were employed to investigate its genomic profile. Finally, we conducted bioinformatics methods to performed SSR (simple sequence repeat) prediction based on the genomic data. The genome size of R. micranthum was estimated to be 554.22 Mb. The heterozygosity ratio was 0.93%, and the sequence repeat ratio was calculated to be 49.17%. The clean reads of R. micranthum were assembled into 2281551 scaffolds with a N50 value of 916 bp. A total of 479724 SSR molecular markers were identified in the R. micranthum genome, and 871656 pairs of primers designed for application. Among of them, 100 primer pairs were validated, and 71 primer pairs were successfully amplified. In summary, the R. micranthum genome is complex with high heterozygosity and low repeated sequences. In future whole-genome research in R. micranthum, higher-depth ‘2+3’ (Illumina+PacBio) sequencing may yield better assembly results.